Intestinal colonization with Campylobacter jejuni affects broiler gut microbiota composition but is not inhibited by daily intake of Lactiplantibacillus plantarum - Valečková, Eliška; Sun, Li; Wang, Helen; Dube, Faruk; Ivarsson, Emma; Kasmaei, Kamyar Mogodiniyai; Ellström, Patrik; Wall, Helena (Frontiers in Microbiology, 2023)
Lactobacilli may prevent broilers from colonization with Campylobacter spp. and other gram-negative zoonotic bacteria through lactic acid production and modulation of the intestinal microbiota. This study evaluated the effects of daily intake of Lactiplantibacillus plantarum 256 (LP256) on Campylobacter jejuni (C. jejuni) loads in ceca and feces of C. jejuni challenged broilers, together with the changes in the gut microbiota. Two experiments were conducted using the hybrids broilers Ross 308 (R-308; Experiment 1) for 42 days and Rowan Ranger broilers (RR; Experiment 2) for 63 days. The LP256 strain was administered either via silage inoculated with LP256 or direct supplementation in the drinking water. Concurrently, haylage as a forage similar to silage but without any inoculum was tested. C. jejuni loads in fecal matter and cecal content were determined by plate counts and qPCR respectively. The cecal microbiota, in response to treatments and the challenge, were assessed by 16S rRNA sequencing. Culturing results displayed a significant reduction in C. jejuni colonization (2.01 log) in the silage treatment in comparison to the control at 1 dpi (day post-infection) in Experiment 1. However, no treatment effect on C. jejuni was observed at the end of the experiment. In Experiment 2, no treatment effects on C. jejuni colonization were found to be statistically significant. Colonization load comparison at the peak of infection (3 dpi) to that at the end of the trial (32 dpi) revealed a significant reduction in C. jejuni in all groups, regardless of treatment. Colonization dynamics of C. jejuni in the cecal samples analyzed by qPCR showed no difference between any of the treatments in Experiment 1 or 2. In both experiments, no treatment effects on the cecal microbiota were observed. However, proportional changes in the bacterial composition were observed after the C. jejuni challenge, suggesting that colonization affected the gut microbiota. Overall, the daily intake of LP256 was not effective in reducing C. jejuni colonization in either broiler type at the end of the rearing period and did not cause any significant changes in the birds' cecal microbiota composition.